The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1089/dna.2012.1961
|View full text |Cite
|
Sign up to set email alerts
|

PON1 Q192R and L55M Polymorphisms and Organophosphate Toxicity Risk: A Meta-Analysis

Abstract: Serum paraoxonase (PON1) is an esterase that is involved in the detoxification of organophosphate insecticides. Emerging lines of evidence have shown that functional polymorphisms in the PON1 gene might play a critical role in increasing susceptibility to organophosphate toxicity, but individually published studies showed inconclusive results. This meta-analysis aimed to derive a more precise estimation of the associations between the PON1 polymorphisms and organophosphate toxicity risk. Nine case-control stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The patient also had a mutation in the NAT2 T431C gene, which has also been associated with increased asthma risk [ 26 ]. PON1 mutations have been associated with significantly greater risk of organophosphate pesticide toxicity [ 27 , 28 ]. It is reasonable that the patient’s genetics made him more susceptible to ketoconazole/fluconazole and other chemical exposures, along with other mechanisms described above, such as inhibition of aldehyde dehydrogenase and the P450 enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The patient also had a mutation in the NAT2 T431C gene, which has also been associated with increased asthma risk [ 26 ]. PON1 mutations have been associated with significantly greater risk of organophosphate pesticide toxicity [ 27 , 28 ]. It is reasonable that the patient’s genetics made him more susceptible to ketoconazole/fluconazole and other chemical exposures, along with other mechanisms described above, such as inhibition of aldehyde dehydrogenase and the P450 enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis evaluated the association of organophosphate toxicity risk with the Q192R and L55M polymorphisms, which included nine case-control studies with a total of 1042 patients with organophosphate toxicity and 1014 healthy controls (You et al, 2013). The results indicated that there was an increased risk of organophosphate toxicity among the Caucasian population with PON1 192Q and 55L polymorphisms.…”
Section: Pharmacogenetics Of Pon1mentioning
confidence: 99%
“…However, the results of case-control studies and metaanalyses remain conflicting (Lee et al, 2015;Liu et al, 2012;Menini and Gugliucci, 2014;Pi et al, 2012;Wills et al, 2009;Zintzaras and Hadjigeorgiou, 2004). L55M and Q192R variants have been found to increase the risk of organophosphate toxicity in a population-dependent manner (You et al, 2013). Moreover, decreased PON1 activity has been associated with I102V PON1 polymorphism as well as with the risk alleles of the promoter polymorphisms rs705379 (−108T > C) and rs705381 (−162G > A) across the 5′ regulatory-region (Brophy et al, 2001;Cronin et al, 2007;Marchesani et al, 2003;Morahan et al, 2007b).…”
Section: Pon1 Pon2 and Pon3mentioning
confidence: 99%